Characterization of flavor fingerprinting of red sufu during fermentation and the comparison of volatiles of typical products - Peng Wang; Xiaoran Ma; Wenping Wang; Dandan Xu; Xin Zhang; Jian Zhang; Yong Sun (Food Science and Human Wellness)
Traditional Chinese red sufu is a popular condiment, and typical flavor is an important indicator of sensory qualities in commercial products. In this study, the volatile aroma analysis of Wangzhihe red sufu (WRS) from different fermentation stages and four typical red sufu products from different locations was carried out by gas chromatography-mass spectrometry (GC–MS), gas chromatography-mass spectrometry/olfactory (GC–MS/O), electronic nose (E-nose) and sensory evaluation. Results showed that 106 volatile compounds were identified in Wangzhihe red sufu during fermentation process, in which phenolics and alcohols were dominant at molded and salted phetze stages, while esters and alcohols became predominate at post-fermentation stage. The volatile aroma substances varied at each fermentation stage. Furthermore, 86 volatiles, including 16 aroma-active compounds, were detected in four typical red sufu products. The multivariate analysis results showed the difference in samples from different fermentation stages and typical red sufu products according to GC–MS and E-nose analysis. Combined with flavor omics, discriminant model was established for effective discrimination of samples from different fermentation stages and locations, as well as references to sufu maturity extent. The study presented a new strategy for quality evaluation of red sufu, which could be the supplement to quality evaluation standards. Keywords: Red sufu, Fermentation process, Volatile compounds, HS-SPME-GC–MS, Flavor omics